A FAIR LEADER PERSPECTIVE BUYA HAMKA (REVIEW OF THE WORD 'ULIL AMRI IN SURAH AN NISA: 59) - Limbong, Rahmat IR.; Chandra, Agus Firdaus; Hakim, Lukmanul; Ghazali, Maher bin (Universitas Muhammadiyah Surakarta, 2023)
This paper reviews the interpretation of one of the figures of modern interpretation, in which the interpretation is expected to be a solution to the problems of human life as the Qur'an was revealed as a mercy to the universe. Among the problems is leadership. Among the mufassir figures in Indonesia who have sat in government is Buya Hamka, who not interprets verses indices by getting involved in government. This study aims to find out how Buya Hamka interprets leadership in the Qur'an. The method used is a descriptive analysis where the primary source used is the book of al-Azhar interpretation. The author also explains asbab nuzul verses related to leaders in the Qur'an. Buya Hamka explained the meaning of a leader by using society's social context and conditions at that time and in a global context. Buya Hamka explained that fair leadership is omniscient and submissive to what God commands by providing benefit to the community without any elements to lead them astray.